2012
DOI: 10.1111/cbdd.12042
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Scanning for Studying Structure‐Activity Relationships in Drug Discovery

Abstract: Peptide-based therapeutics have grown in importance over the last few decades. Furthermore, peptides have been extensively used as lead compounds in the drug discovery process to investigate the nature of chemical space required for molecular recognition and activity at a variety of targets. This critical commentary reviews scanning techniques, which employ natural and non-proteinogenic amino acids to facilitate understanding of structural requirements for peptide biological activity. The value of sequence ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 105 publications
(220 reference statements)
1
66
0
Order By: Relevance
“…This can be conceptualized as a scanning approach, 12 where one can deliberately vary the positions of two amino acids as well as the chemical and topological composition of the entity connecting these two residues (Figure 1). To develop a versatile peptide macrocyclization scan, we believe synthetic convergence and site-independent reactivity are required.…”
Section: Introductionmentioning
confidence: 99%
“…This can be conceptualized as a scanning approach, 12 where one can deliberately vary the positions of two amino acids as well as the chemical and topological composition of the entity connecting these two residues (Figure 1). To develop a versatile peptide macrocyclization scan, we believe synthetic convergence and site-independent reactivity are required.…”
Section: Introductionmentioning
confidence: 99%
“…Staple scanning echoes the alanine scanning technique by also helping to determine if a residue is required for binding affinity. 50 This strategy has been used to identify a selective inhibitor of MCL-1, a human cancer resistance factor. 43 Stewart et al found that the peptide, which had the highest α-helical character, as shown by CD, also had the highest binding affinity for MCL-1.…”
Section: Staple Scanningmentioning
confidence: 99%
“…The "D-scan" is a simple synthetic method to investigate the conformationactivity relationships of a peptide [50]. Following this strategy, Paterlini et al [51] synthesized a series of diastereoisomers of EM-1 [d-Tyr 1 -d-Pro 2 -d-Trp 3d-Phe 4 -EM-1] without an improvement of potency in respect to the parent drug.…”
Section: Stereoisomers and Proline Residue Modifications Of Endomorphinsmentioning
confidence: 99%